pengaruh pemahaman peraturan perpajakan, kualitas pelayanan, kesadaran wajib pajak dan sanksi pajak terhadap kepatuhan wajib pajak orang pribadi. - Nur Ghailina As'ari (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to determine the effect of understanding tax laws, service quality, taxpayer awareness, and tax sanctions on taxpayer compliance of individuals at the District Rongkop, district Gunungkidul. This research type is quantitative research by using primary data. The population in this study is all taxpayers of individuals registered in KPP Pratama Wonosari. Especially Individual Taxpayers in Rongkop Subdistrict and the criteria of respondents in the study are registered Private Taxpayers. Data collection was done directly by using. Data analysis in this research using multiple regression with SPSS program version 16.0. The results showed that the value of F arithmetic 27.707 greater than F table 2.49. These results indicate that the understanding of tax laws, service quality, taxpayer awareness, and tax sanctions affect simultaneously to the compliance of individual taxpayers. In persial understanding of tax regulations (X1) and tax penalties (X4) have a significant positive effect on taxpayer compliance of individuals. This result is proved by t count> t table 1,66543 and significance <0,05, that is (a) 3,061 and 0,003 (X1Y), (b) 2,219 and 0,03 (X4Y). The quality of service and awareness of the taxpayer has no significant effect on the taxpayer compliance of the individual. This is evidenced by the value of t arithmetic <t table 1.66543 and significance> 0.05, ie (a) 0.814 and 0.218 (X2Y) and (b) 1.389 and 0.169 (X3Y). Keywords: Understanding of taxation regulation, service quality, taxpayer awareness, and tax sanction on personal taxpayer compliance.